Controversies relating to preparticipation cardiovascular screening in young athletes: time for a realistic solution? - Papadakis, M.; Chandra, N.; Sharma, S. (British Journal of Sports Medicine, 2011)
The sudden death of any young individual is a tragic event that causes immeasurable damage to family lives. The sudden death of a young athlete from a cardiac disorder is particularly emotive and is often associated with considerable media coverage, drawing attention to the youth, the athletic prowess of the individual and the number of life years lost consequent to a cardiac disorder that could have been detected during life. Most exercise-related sudden cardiac deaths (SCDs) are attributed to congenital or hereditary cardiac disorders that are asymptomatic in most victims.1 2 Unsurprisingly, the death of a young athlete often galvanises urgent discussions relating to preparticipation cardiac screening involving members of the community, sports physicians and sporting governing bodies.